Gastric Electrical Dysarrhythmia in Probable Rapid Eye Movement Sleep Behavior Disorder - Peng, Anjiao; Ji, Shuming; Li, Wanling; Lai, Wanlin; Qiu, Xiangmiao; He, Shixu; Dong, Bosi; Huang, Cheng; Chen, Lei (Frontiers in Neurology, 2021)
Background: Subjective gastrointestinal complaints have been repeatedly reported in patients with REM sleep behavior disorder (RBD), but objective evidence is scarce. We aimed to objectively investigate the gastrointestinal dysfunction in individuals with probable RBD (pRBD) using electrogastrogram. Methods: Thirty two participants with pRBD and 60 age and gender- matched healthy controls were enrolled. pRBD was diagnosed based on questionnaires and further assessed by experienced neurologists. After thorough assessment of participants' subjective gastrointestinal symptoms, preprandial and postprandial gastric activities were measured using electrogastrogram. Dominant frequency, dominant power ratio, and the ratio of preprandial to postprandial power were analyzed. Results: Among the gastric symptoms, hiccup (34.8% vs. 9.6%, p = 0.017) and postprandial gastric discomfort (43.5% vs. 15.4%, p = 0.017) were more frequent in participants with pRBD than in controls. The dominant frequency on the electrode overlying the gastric pyloric antrum was lower in pRBD than in healthy controls (2.9 [2.6 - 2.9] vs. 2.9 [2.9 - 3.2] cpm, p = 0.006). A reduced dominant power ratio from the same electrode was also found in individuals with pRBD (60.7 [58.0 - 64.5] vs. 64.2 [58.7 - 69.6] %, p = 0.046). Conclusions: Patients with pRBD have a higher rate of gastric dysfunction which presented as irregular slow wave rhythmicity on electrogastrogram.